Role of Lipopolysaccharide Phase Variation in Susceptibility of Haemophilus influenzae to Bactericidal Immunoglobulin M Antibodies in Rabbit Sera - Erwin, Alice L. (American Society for Microbiology, 2000)
The effect of phase variation of lipopolysaccharide (LPS) structure on the susceptibility of Haemophilus influenzae to complement-dependent killing by normal human sera and normal rat sera has been described previously. The phase-variable structure phosphorylcholine (ChoP) confers susceptibility to human serum, since ChoP on the bacterial cell surface binds to serum C-reactive protein and activates complement. In contrast, expression of galα1,4gal, a second phase-variable epitope that is also found on human glycoconjugates, confers resistance to human serum. We studied the role of phase variation of these structures in the susceptibilities of H. influenzae KW20 (Rd) and a clinical isolate of nontypeable H. influenzae to killing by rabbit sera, which often possess naturally acquired complement-dependent bactericidal activity for unencapsulated H. influenzae. Expression of ChoP increased the resistance of strain KW20 to killing by bactericidal rabbit sera. In contrast, the serum resistance of a clinical isolate, H233, was unaffected by ChoP expression but was reduced by galα1,4gal expression. The rabbit sera with bactericidal activity (but not the nonbactericidal sera) all contained immunoglobulin M (IgM) antibodies able to bind to the surface of H. influenzae bacteria, as detected by flow cytometry, and contained IgM antibodies to LPS purified from strain KW20. Preincubation of sera with LPS reduced their bactericidal activity. Bactericidal activity was recovered quantitatively in an IgM-enriched fraction of sera. It is concluded that naturally occuring bactericidal activity for unencapsulated H. influenzae is largely due to IgM antibodies directed against phase-variable structures of the LPS.